Mutual Authentication Scheme Based on Lattice for NFC-PCM Payment Service Environment - Sung-Wook Park; Im-Yeong Lee (International Journal of Distributed Sensor Networks, 2016)
In recent years, the incorporation of NFC (Near Field Communication) technology into mobile devices has led to changes in payment system environments. Currently, the NFC mobile payment service is leading the mobile payment market. In particular, most electronic payment services, such as those used by Google Inc. and Apple Inc., are adopting payment methods based on NFC to replace credit cards. In addition, related groups from the Republic of Korea have enhanced safety in communication by using standard techniques for activating NFC services. However, various security threats are still present in electronic payment methods that use NFC. In this paper, we propose a mutual authentication scheme based on a lattice for conditional anonymity in NFC-PCM (Near Field Communication-Passive Communication Mode) payment services environments.